Adsorption of Ibuprofen from Water Using Waste from Rose Geranium (Pelargonium graveolens) Stems - Ntaote David Shooto; Patience Mapule Thabede (Applied Sciences)
Rose geranium is widely used for oil extraction and in the food, perfume, and pharmaceutical industries. The waste produced after oil extraction has no alternative use and is usually dumped into the environment, causing pollution. This study aimed to use waste rose geranium stems (SPG) as a potential adsorbent for ibuprofen from water. The adsorbent was characterised by SEM-EDX, FTIR, TGA, and BET. The SEM images showed that the adsorbent had a rough surface with voids and pores. Different functional groups were detected on the surface of SPG with FTIR. The trend of IBU adsorption showed that the adsorption capacity increases when the initial concentration of working standards is increased. The data for the contact time effect show that the adsorption rate was fast in the initial stage between 1 and 45 min. Afterward, a slow adsorption rate occurred between 65 and 105 min. The kinetic data corresponded to the Langmuir and pseudo-first-order (PFO) models. The highest recorded IBU uptake was 34.88 mg/g. The ΔHo value shows that the adsorption of IBU on SPG was controlled by physisorption. The obtained values of ΔGo are negative, indicating that the uptake of IBU was spontaneous.